Sibling Rivalry and Psychological Well-Being in Early Adulthood - Umar, Livia; Savitri, Setiawati Intan (Universitas Mercu Buana Jakarta, 2026)
Many cases of sibling rivalry, including crimes, are committed by young adults who are usually considered independent, responsible and have good psychological well-being. These cases are caused by parental injustice. Parenting patterns that create sibling rivalry. This study aims to determine whether there is a significant relationship between sibling rivalry and psychological well-being in early adults in Jakarta. The research method used is quantitative with the criteria for male or female, aged 18-29, having at least one sibling and domiciled in Jakarta. Sibling rivalry was measured using the ASRQ Rivalry Subscale (Stocker, 1997), adapted via expert judgment, while psychological well-being used the SPWB (Ryff & Keyes) adapted by Fadhil (2021). The 114 respondents were obtained and analyzed using SPSS and Spearman's rho correlation test. The results showed no significant relationship between sibling rivalry and psychological well-being. This means that higher levels of sibling rivalry do not necessarily increase or decrease psychological well-being, and vice versa. However, in the correlation matrix, sibling rivalry correlated positively with the Positive Relations with Others dimension and negatively with the Personal Growth dimension.